(untitled) (Revista Argentina de Musicología, 2012)
This performative genre, which is known as ‘payada rioplatense’, is part of the broader phenomenon of poetic-musical traditions in which the improvisation of the text plays a fundamental role. It takes the form of challenges in which two or more payadores alternate on stage, improvising to the sound of the guitar. This article discusses some aspects of poetic improvisation in contemporary payada, with special emphasis on its consideration as a performative genre and revealing some of the rules and processes that come into play during a challenge between two professionals. To do so, the major structures according to which improvisation develops will be introduced, and an analysis of the interactions between these structures during the performance will be proposed, with the aim of understanding some of the mechanisms involved in the determination of performance as a unique event. The study of contemporary performance and its location in the historical context of the tradition allows me to advance some hypotheses about what has been the linchpin of the changes which modified the tradition in the province of Buenos Aires since its professionalization at the end of the nineteenth century.